Народознавство: прикладний аспект - Бондаренко, Г. (Народна творчість та етнографія, 2007)
The critical state of the modern Ukrainian society reveals not only in economics and politics but also in spiritual and cultural spheres. School and education in general play a great role in the formation of the next generations. In May of 2007 the Rylsky Institute initiated and conducted the conference “National Factor in the System of the Modern Education”, which gave a chance to teachers and scholars to communicate up closely, in order to share ideas and personal experience. Teachers described the new topic and themes included in the school program in area of folklore and cultural studies, such as Ukrainian rite and ritual culture, sacral architecture, Diaspora’s folklore, Cossack life and folklore and others.